INTERNALISASI EKSTERNALITAS PAJAK KARBON : TINJAUAN LITERATUR SISTEMATIS - Suryati, Tri Frida; S Mooduto, William Indra (Paser Institute Of Accounting and Finance, 2024)
This systematic literature review examines the internalization of carbon tax externalities by referring to scientific articles, empirical studies, theoretical frameworks, and practical insights to find effective strategies for implementing carbon tax in Indonesia. Carbon tax has been proven to be an effective instrument in reducing carbon emissions in various countries, such as Sweden, British Columbia in Canada, and the European Union. Sweden, for example, has significantly reduced per capita CO2 emissions without hindering economic growth since implementing the carbon tax in 1991 with an initial rate of around 30 per ton of CO2. British Columbia has also recorded similar success with its revenue-neutral carbon tax introduced in 2008. Nonetheless, challenges in implementing carbon taxes remain, including carbon price fluctuations and political resistance, as seen in Australia. The Indonesian government enacted two regulations related to carbon tax in 2021: Presidential Regulation No. 98 of 2021 on the Implementation of Carbon Economic Value and Law No. 7 of 2021 on the Harmonization of Tax Regulations as part of efforts to mitigate climate change. This systematic literature review highlights the importance of effective policy design and proper implementation in internalizing carbon tax externalities in Indonesia, which is crucial for achieving climate change mitigation goals.